Association and Interaction Effect between VEGF Receptor-2 (VEGFR-2) Gene Polymorphisms and Dietary Pattern on Blood Lipids in Malaysian Adults - Yap, Roseline Wai Kuan; Masaki, Motofumi; Shidoji, Yoshihiro; Hon, Wei Min (Journal of Nutritional Therapeutics, 2014)
Background: Vascular endothelial growth factor receptor-2 (VEGFR-2) and diet are related to blood lipid health. Gene-diet interaction studies can identify the risks. The objectives are to determine associations, and interaction effects between VEGFR-2 gene polymorphisms (rs1870377 and rs2071559) and dietary patterns on blood lipids in multi-ethnic Malaysian adults. Methods: Dietary intakes of 509 (153 Malay, 179 Chinese, and 177 Indian) Malaysians were obtained from food frequency questionnaire for the construction of dietary patterns using factor analysis. Anthropometric measurements: body mass index and blood pressure; and biomarkers: glycated hemoglobin, total cholesterol (TC), triglycerides (TG), low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), and total cholesterol/HDL-C ratio were determined. Genotyping of rs1870377 and rs2071559 was performed by real-time PCR using Taqman probes. Results: Two major dietary patterns were extracted from all subjects: ‘Vegetables, fruits, and soy diet’ (VFSD), and ‘Rice, egg, and fish diet’ (REFD). There were significant genetic associations for rs2071559 with TG (p=0.048) in Malays, and in Chinese for rs1870377 with TC (p=0.001) and LDL-C (p=0.007), and rs2071559 on LDL-C (p=0.048). The interaction effects of VEGFR-2 gene polymorphisms and dietary patterns were significant in Malays between rs2071559 and REFD on TG (p=0.005); and in Chinese between VFSD and rs1870377 on LDL-C (p=0.028) after adjusting for potential confounders. There were no significant genetic or dietary associations on blood lipids in Indians (p>0.05). Conclusion: The significant associations and gene-diet interaction effects between VEGFR-2 gene polymorphisms and dietary patterns on blood lipids may pose hyperlipidemia and hypercholesterolemia risks in Malay and Chinese Malaysians